Obstacle Detection on Autonomous Driving Systems - S, Vignesh; Karunya, K; P, Vijaya Sankar K; Shabu, S L Jany; Poornima, D (2025 International Conference on Advanced Computing Technologies (ICoACT), 2025)
Self-driving cars, also known as autonomous vehicles are capable of supplanting automobiles driven by humans. In situations that humans find difficult, autonomous vehicles are able to examine their surroundings and ease through roadways. Many people might soon turn very dependent on AVs and overconfident that there won't be any failures owing to this. This has resulted in AVs having both affirmative as well as bad hands on the society. A combination of hardware, software, people, and their interactions, AVs are X-ware systems. There are still a lot of unanswered questions regarding AVs despite the abundance of research on the subject. Communication with pedestrians and other cars on the road is one of the biggest problems facing AVs. There must be an interaction between AVs and other transport users if autonomous cars have to replace human- driven vehicles. Few previous studies have examined the role of humans in the present shift to a society where self-driving cars are the norm, whereas the majority have focused on software errors. Three perspectives are examined in this paper: I that of the AV's driver and passenger; II that of pedestrians; and III that of the AV's interactions with other users of the transportation network. We also talk about relevant behavioral research.